2005
DOI: 10.1177/1362361305051395
|View full text |Cite
|
Sign up to set email alerts
|

Social communication in children with autism

Abstract: This longitudinal study investigated the developmental trajectory of discourse skills and theory of mind in 57 children with autism. Children were tested at two time points spaced 1 year apart. Each year they provided a natural language sample while interacting with one parent, and were given standardized vocabulary measures and a developmentally sequenced battery of theory of mind tasks. The language samples were coded for conversational skills, specifically the child's use of topic-related contingent utteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(45 citation statements)
references
References 46 publications
2
41
1
1
Order By: Relevance
“…This finding provides further support for the ToM account of ASD. Likewise, these findings are consistent with Hale and Tager-Flusberg (2005) who found, using hierarchical regressions, that independent of age, language, and IQ, ToM contributes unique variance in discourse skills among children with ASD. The only narrative measure that ToM did not uniquely predict was cohesion of the script-based story, which may have been due to the reduced variability among cohesion scores in children with ASD on this task in comparison to the non-script based story.…”
Section: Relationship Between Individual Characteristics and Narrativsupporting
confidence: 80%
“…This finding provides further support for the ToM account of ASD. Likewise, these findings are consistent with Hale and Tager-Flusberg (2005) who found, using hierarchical regressions, that independent of age, language, and IQ, ToM contributes unique variance in discourse skills among children with ASD. The only narrative measure that ToM did not uniquely predict was cohesion of the script-based story, which may have been due to the reduced variability among cohesion scores in children with ASD on this task in comparison to the non-script based story.…”
Section: Relationship Between Individual Characteristics and Narrativsupporting
confidence: 80%
“…According to Brown, a morpheme is acquired when it is used correctly in 90% of obligatory contexts (Brown, 1973). Because we were concerned with children’s initial usage and developmental trajectory of these morphemes, and not necessarily when they had reached adult-like levels, we coded for number of correctly used morphemes rather than their use in obligatory contexts (Capps, Kehres, & Sigman, 1998; Hale & Tager-Flusberg, 2005). For example, an utterance such as “I goed to the zoo,” which is an incorrect usage of the irregular past went , was not included in our analysis as a regular past tense marker.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who fail false belief tasks (Baron-Cohen et al 1985) have been found to show less insightful social behaviour and poorer verbal communication skills (Frith 1994). Furthermore, performance on measures of perspective-taking have been associated with skills required for appropriate social behaviour, including ability to maintain conversation and respond appropriately (Hale and Tager-Flusberg 2005), to contribute novel information (Capps et al 1998), to understand non-literal language (Martin and MacDonald 2004), and to identify others’ embarrassment (Hiller and Allinson 2002). Individuals with ASD have been found to be impaired in all of these areas.…”
Section: Introductionmentioning
confidence: 99%